Recycling of Walnut Shell Biomass for Adsorptive Removal of Hazardous Dye Alizarin Red from Aqueous Solutions Using Magnetic Nanocomposite: Process Optimization, Kinetic, Isotherm, and Thermodynamic Investigation - Vairavel Parimelazhagan; Palak Sharma; Yashaswini Tiwari; Alagarsamy Santhana Krishna Kumar; Ganeshraja Ayyakannu Sundaram (ChemEngineering)
Dye wastewater poses significant risks to human health and aquatic ecosystems, necessitating efficient remediation strategies. This study developed a magnetic Fe2O3 nanocomposite (MNC) derived from phosphoric acid-treated walnut shell biomass carbon to remove Alizarin red S (AR) dye from polluted water. Characterization techniques confirmed the nanocomposite’s mesoporous structure, superparamagnetic properties (61.5 emu/g), and high crystallinity. Optimization using Response Surface Methodology (RSM) revealed a maximum adsorption efficiency of 94.04% under the following optimal conditions: A pH of 2, AR dye concentration of 85 mg/L, adsorbent dose of 1.5 g/L, and particle size of 448.1 nm. Adsorption followed pseudo-second-order (PSO) kinetics (R2 = 0.9999) and Langmuir isotherm models (R2 = 0.9983), with thermodynamic studies indicating spontaneous and endothermic chemisorption. The intra-particle diffusion model, Bangham, and Boyd plots describe the adsorption process, and external boundary layer diffusion of AR dye molecules in the aqueous phase limits the adsorbate removal rate. Regeneration tests demonstrated reusability over three cycles, with a desorption efficiency of 50.52% using 30 mM HCl. The MNC exhibited a maximum adsorption capacity (Qmax) of 115.35 mg/g, outperforming other adsorbents, making it an efficient and sustainable alternative solution for AR dye removal from water bodies.